Analysis of Transition Mode from Phase-Shift to Zero Phase-Shift under ZVS and NON-ZVS Operation for Induction Heating Inverter - Pichetjamroen Viriya; Naras Yongyuth; Kouki Matsuse (My University, 2008)
This paper proposes an analysis of transition mode from phase-shift to zero phase-shift under ZVS and NON-ZVS operations for a series resonant inverter with the load of induction heating. A number of circuit operations during transition mode from phase-shift to zero phase-shift under ZVS and NON-ZVS conditions are first analyzed. Various voltage and current equations of the operating circuits are then obtained and used for calculation of the waveforms by the aid of MATLAB program. The calculated waveforms make possible the consideration of some important circuit parameters that are used to determine ZVS or NON-ZVS conditions. The theoretical results and proposed method are also verified by experimental ones, using a prototype test set in our laboratory.
Keywords: Induction Heating; Mode (computer interface); Zero (linguistics); Induction Heating and Inverter Technology